2014
DOI: 10.1155/2014/257930
|View full text |Cite
|
Sign up to set email alerts
|

Anti-HMGB1 Neutralizing Antibody Ameliorates Neutrophilic Airway Inflammation by Suppressing Dendritic Cell-Mediated Th17 Polarization

Abstract: We demonstrate that high mobility group box 1 protein (HMGB1) directs Th17 skewing by regulating dendritic cell (DC) function. First, our in vitro studies reveal that recombinant HMGB1 (rHMGB1) activates myeloid DCs to produce IL-23 in vitro, and rHMGB1-activated DCs prime naïve lymphocytes to produce the Th17 cytokine IL-17A. Second, we demonstrate that anti-HMGB1 neutralizing antibody attenuates HMGB1 expression, neutrophilic inflammation, airway hyperresponsiveness, and Th17-related cytokine secretion in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 33 publications
1
29
0
Order By: Relevance
“…In addition to regulation of monocytic populations of cells, in allergic lung inflammation (42) recent data suggest that HMGB1 directs Th17 skewing by regulating dendritic cell function, suggesting that HMGB1 drives the DC-polarized Th17-type response and that blocking HMGB1 may be beneficial in attenuating neutrophilic airway inflammation in asthma via this mechanism. The latter was not investigated in the current study reported herein, but suggests another possible indirect role for HMGB1 in recruitment of PMN during bacterial keratitis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to regulation of monocytic populations of cells, in allergic lung inflammation (42) recent data suggest that HMGB1 directs Th17 skewing by regulating dendritic cell function, suggesting that HMGB1 drives the DC-polarized Th17-type response and that blocking HMGB1 may be beneficial in attenuating neutrophilic airway inflammation in asthma via this mechanism. The latter was not investigated in the current study reported herein, but suggests another possible indirect role for HMGB1 in recruitment of PMN during bacterial keratitis.…”
Section: Discussionmentioning
confidence: 99%
“…HMGB1 can modulate the inflammatory response in the airway diseases by inducing MUC8 expression in airway epithelial cells (Kim et al, 2012) and mediating cytokine production via Toll-like receptor 4 in acute lung injury (Deng et al, 2013). Moreover, HMGB1 protein was shown to be an important mediator in asthma since its inhibition by neutralizing antibodies lowered many inflammatory responses in mice lung (Zhang et al, 2014). Thus, HMGB1 may be a desirable target to be down-regulated in asthma and other respiratory diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the concentrations of HMGB1 in asthmatic and COPD (chronic obstructive pulmonary disease) patients positively and significantly correlated with neutrophils counts and percentage of neutrophils in sputum (Hou et al, 2011). In another study, it has been demonstrated that HMGB1 neutralizing antibody attenuates neutrophilic inflammation in vivo by using a murine model of neutrophilic asthma induced by ovalbumin plus lipopolysaccharide (Zhang et al, 2014). However, the role of HMGB1 in respiratory diseases is still elusive but nevertheless these studies suggest an involvement of this cytokine in their pathogenesis.…”
Section: Introductionmentioning
confidence: 97%
“…HMGB1 ligation of RAGE, TLR-2, or TLR-4 results in the activation of nuclear factor-kB and neutrophilic inflammation (10). HMGB1 also contributes to chronic neutrophilic inflammatory airway disease by blunting macrophage phagocytosis and clearance of bacteria (11), inhibiting phagocytosis of apoptotic neutrophils (12), promoting neutrophil extracellular trap formation (13), and inducing dendritic cell-mediated Th17 polarization (14). Although HMGB1 is a potential therapeutic target for reducing excessive inflammation in chronic airway diseases, there are currently no therapies that target HMGB1 inhibition.…”
Section: Clinical Relevancementioning
confidence: 99%